A new genus Austrimonus for Eutettix melaleucae Kirkaldy (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini) and nine new species - Fletcher, Murray J.; Dai, Wu (Zootaxa, 2018)
The new genus Austrimonus is created for Eutettix melaleucae Kirkaldy, previously in Hishimonus Ishihara, and the species redescribed as Austrimonus melaleucae (Kirkaldy), comb. nov. Nine new Australian species are added to the genus: A. apicalis sp. nov., A. biapicalis sp. nov., A. bidentatus sp. nov., A. clavatus sp. nov., A. curvatus sp. nov., A. flagellatus sp. nov., A. koebelei sp. nov., A. litorus sp. nov. and A. luteus sp. nov. A key for the determination of males of the species is provided.